Analysis of near cortex versus both cortex screw fixation in bone fracture surgery - a finite element study - Soh, Cheng Siong (2016)
A bone fracture is a discontinuity of a bone due to damages likely from external forces. The healing of the fracture can be accelerated with the use of locking compression plates (LCP) held into place with suitable locking screws. They prevent unnecessary movement while holding on optimal stress at the fractured area to promote healing with increased blood supply and preventing damage to the surface of the bone. The aim of the project seeks to analyse the behaviour of overdrilled near cortex versus both cortex screw fixation in bone fracture surgery. Finite Element (FE) analysis of the LCP and plate-bone construct were modelled and simulated the LCP model is determined to be sufficiently accurate with bending rigidity and axial stiffness within the 5% margin of error from the experiment. The aim of the project aims to project seeks to study the effect of trapezoid near cortex over-drilled holes on a plate-bone construct compared to the Figure-of-8 hole configuration and the control plate-bone construct with no over-drilled holes. Torsional rigidity, bending rigidity, axial stiffness, and axial strength was calculated from experiments. The readings will help towards the development of an accurate FEM plate-bone construct to determine the optimal size and type of over-drilled holes to reduce stiffness and accelerate the bone healing process. When compared with the Chen et al., [28] control bone construct with only both cortical locking, the trapezoid over-drilled hole have a 6.33% higher bending rigidity, 13.15% lower axial stiffness and 8.47% higher axial strength.